Phlegmonous Psoas Muscle Infection Causing Sepsis and Death With Missing Postmortem Computed Tomography Scan Correlation. (June 2021) - Garland, Jack; O'Connor, Kate; Hu, Mindy; Ondruschka, Benjamin; Tse, Rexson
Abstract : Abstract: Infection of the psoas muscle is a rare pathology, which carries a high risk of sepsis and is a potential cause of death. Classic symptoms include back pain and fever and it may be diagnosed premortem on computed tomography or magnetic resonance imaging, where abscess formation may be identified as a discrete rim enhancing and low-attenuation lesion. Infections without abscess formation, such as phlegmonous infection, may be more difficult to identify however, particularly if there is absence of other nonspecific findings, such as gas bubbles. We report a case of Staphylococcus aureus phlegmonous psoas muscle causing sepsis and death with no postmortem computed tomography scan correlation, where clinical history of back pain and an unknown source of sepsis was the only prompt for psoas dissection. This case highlights a potential postmortem computed tomography blind spot in abdominal pathology and we recommend dissecting the psoas muscle if sepsis is suspected but a definitive septic focus is unable to be identified.